INOVASI PELAYANAN PUBLIK STUDI KASUS â€œMOTOR PELAYANAN LORONG TAâ€ PADA KANTOR KECAMATAN RAPPOCINI KOTA MAKASSAR - Mutiara Pratiwi; Alam Tauhid Syukur (Politeknik STIA LAN Makassar, 2018)
This study aims to find out how the implementation of public service innovation is a case study of Motor Pelayanan Lorong Taâ€™ at Rappocini District Office of Makassar City. Has the implementation run in accordance with the values of public services or the other way, And what kind of procedures must be carried out by community to use this service. This study used a case study method with a qualitative approach and the unit of analysis in this study were the employees of the Rappocini Sub-district of Makassar City in this case the Head of the Sub-District, Secretary of the Sub-District and Motor Driver of the â€œMotor Pelayanan Lorong Taâ€ and some of the Rappocini Subdistrict communities.The results of the study show that the â€œMotor Pelayaan Lorong Taâ€ is already good enough just about timeliness,the lack of human resources and infrastructure provided by the sub-district is enough to be an obstacle in the implementation of these innovations so that this innovation cannot be said to be effective and efficient in providing services to the community. Suggestions that can be give to the sub-district is adding more human resources and infrastructure so there is no delay in serving the community and no more wait longer.